A new species of Dignomus Wollaston (Coleoptera: Ptinidae) from Eocene Baltic amber - Bukejs, Andris; Bellés, Xavier; Alekseev, Vitalii I. (Zootaxa, 2018)
Dignomus francescovitalii sp. nov. is described and illustrated based on a well-preserved specimen from Eocene Baltic amber. This new extinct species is placed into D. irroratus species-group. The distribution of the genus Dignomus including fossil records is mapped.